2018
DOI: 10.1007/s11142-018-9460-4
|View full text |Cite
|
Sign up to set email alerts
|

Financial reporting in hyperinflationary economies and the value relevance of accounting amounts: hard evidence from Zimbabwe

Abstract: We examine the relative and incremental value relevance of inflation-adjusted (IA) and historical cost (HC) amounts in a hyperinflationary economy. Using an innovative setting and a unique dataset drawn from annual reports of firms listed on the Zimbabwe Stock Exchange for the 2000-2005 period, we find that both sets of amounts are value relevant, but HC amounts are superior to IA amounts. We also show that inflation gains and losses provide incremental information content beyond that provided by the HC amount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 59 publications
(142 reference statements)
0
2
0
Order By: Relevance
“…Bulow and Shoven (1982) highlighted challenges arising from high and volatile inflation during the 1960s and 1970s, leading to distortions in financial accounts. Comparing the inflation-adjusted and historical cost amounts, Chamisa et al (2018) found that gains and losses in hyperinflationary economy provide incremental information beyond the historical cost amounts. This means financial statements reflect historical amounts that are not adjusted under inflationary conditions (Kramarova, 2021;Frank 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bulow and Shoven (1982) highlighted challenges arising from high and volatile inflation during the 1960s and 1970s, leading to distortions in financial accounts. Comparing the inflation-adjusted and historical cost amounts, Chamisa et al (2018) found that gains and losses in hyperinflationary economy provide incremental information beyond the historical cost amounts. This means financial statements reflect historical amounts that are not adjusted under inflationary conditions (Kramarova, 2021;Frank 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Given the principles covered in IAS 29, several authors applied the concepts to numerical terms (Goldschmidt & Yaron, 1991), as needed in the accounting field. Empirical evidence mostly describes the characteristics of hyperinflationary economies (Pittaluga et al, 2021;Reinhart & Savastano, 2003;Coomer & Gstraunthaler, 2011;Lopez & Mitchener, 2021), effects and implications of IAS 29 (Tamimi & Orbán, 2020;Obstfeld & Rogoff, 2021;Marthinsen & Gordon, 2022) and implications of IAS 29 on financial reporting (Chamisa et al, 2018;Ovidiu et al, 2013). There are only few studies on applying IAS principles to company net assets.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Gordon (2001) reports that in Mexico, a high inflation economy, GPLA, CCA, and historical cost accounting numbers are all value relevant. Chamisa et al (2018) show that in Zimbabwe, a hyperinflationary economy, both historical cost and inflation adjusted amounts are value relevant, but historical cost amounts are superior to inflation adjusted amounts during lower 7 IAS 29 Accounting in Hyperinflationary Economies requires GPLA adjustments whether a firm's underlying accounts are at historical cost or at current cost. One test for a hyperinflationary economy is that inflation exceeds 100% over a three-year period (other tests also exist).…”
mentioning
confidence: 99%
“…Chamisa et al . (2018) show that in Zimbabwe, a hyperinflationary economy, both historical cost and inflation adjusted amounts are value relevant, but historical cost amounts are superior to inflation adjusted amounts during lower inflationary periods (average annual inflation 91%) and are equal during very high inflationary periods (average annual inflation 369%).…”
mentioning
confidence: 99%